Storage stability of Lactobacillus paracasei as free cells or encapsulated in alginate-based microcapsules in low pH fruit juices - Rodrigues, Dina (2019)
The main objective of this research effort was to study whether microencapsulation could be a viable alternative to obtain probiotic orange or peach juices. In order to be considered probiotic food, probiotic bacteria must be present in sufficient viable numbers to promote a benefit to the host. The survival and viability of Lactobacillusparacasei L26 in juices over 50 days of storage at 5°C was assessed, evaluating the potential use of encapsulated cells in alginate microcapsules. L. paracasei L26 demonstrated good viability in both orange and peach juices despite the low pH values of both juices. Microencapsulation in alginate, with or without double coating, revealed to be suitable to protect L. paracasei L26 since viable cells were approximately 9 log cfu/g after 50 days of storage at 5°C. In general, the probiotic fruit juices showed a decrease in pH during storage. Glucose and fructose contents as well as citric acid contents decreased during storage, whereas an increase in formic acid was observed. The outcome of this study points to L. paracasei L26 as having promising potential, especially in an encapsulated form, as functional supplements in fruit juices without dairy ingredients due to their tolerance in an acidic environment over 50 days of storage at 5°C. Further studies are warranted to prove the functionality of juices with encapsulated probiotic strains.